NUTRITION CONSUMPTION STANDARDS IN EUROPEAN UNION COUNTRIES AND POLAND IN THE PERIOD 1990-2000 - Borowska, Agnieszka (Acta Scientiarum Polonorum. Oeconomia, 2002)
The paper discusses the changes in the consumption of some basic products of the plant and animal origin in European Union and in Poland in the period of 1990-2000. The patterns of food consumption in EU were analysed. The classification of patterns was worked out on the basis of differences and similarities to the EU’s consumption. Some elements having impact on the consumption in Poland in the nineties, during the period of Polish negotiations with EU were also discussed.